LIFE STYLE: MAHASISWA UIN SYAHADA PADANGSIDIMPUAN TERHADAP KESEHATAN MENTAL - Nur Mawaddah Warohmah (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to explore the lifestyle of UIN Syahada Padangsidimpuan students and its relationship with their mental health. The method used was a survey of a randomly selected sample of students. The variables studied include diet, physical activity, sleep patterns, and social media usage. Data were analyzed using descriptive and inferential statistical techniques. The results showed that most students tend to have an unhealthy diet, lack of physical activity, and irregular sleep. In addition, excessive social media use was also found to be associated with higher levels of stress and anxiety. These findings indicate the need for interventions to improve students' understanding and behavior in maintaining their mental health.